Occupational skin dermatosis among dental lab technicians in Khartoum state, 2023-2024 - Abbas, Razan Mohamed Alamin; Magzoub, Abdelrahman; Alagraa, Bakri Al; Almuutairi, Nawaf (International Journal of Research in Dermatology, 2025)
Background: Occupational skin dermatosis is of a significant concern among dental lab technicians due to their exposure to chemicals and materials used in dental prosthetics. These exposures can lead to various skin conditions, impacting the health and productivity of the workforce. To determine the prevalence, clinical features and associated factors of occupational skin dermatosis among dental lab technicians in Khartoum State from 2023 to 2024. Methods: A descriptive, observational, cross-sectional study was conducted among 171 dental lab technicians in Khartoum State. Data collection involved a structured questionnaire, including demographic information, clinical features of skin conditions and use of protective equipment. Analysis was performed using SPSS Version 26, with descriptive and inferential statistics applied to identify significant associations. Results: Of the 171 participants, 85.4% reported work-related skin symptoms, with dry skin being the most prevalent symptom (100%). Contact with denture material, particularly methyl methacrylate (MMA), was implicated in all reported cases. The use of protective equipment was low, with only 34.2% of participants using gloves or masks regularly. The prevalence of symptoms was significantly associated with the use of MMA and inadequate protective measures. Conclusions: The study underscores a high prevalence of occupational skin dermatosis among dental lab technicians in Khartoum State, highlighting the need for improved occupational health practices. Implementing training programs on the proper use of protective equipment and regular monitoring of skin health are recommended to mitigate these risks.